A unified approach to reduce SOC test data volume, scan power and testing time. - Chandra, A. (IEEE Transactions on computer-aided design of integrated circuits and systems)
We present a test resource partitioning (TRP) technique that simultaneously reduces test data volume, test application time, and scan power. The proposed approach is based on the use of alternating run-length codes for test data compression. We present a formal analysis of the amount of data compression obtained using alternating run-length codes. We show that a careful mapping of the don't-cares in precomputed test sets to 1's and 0's leads to significant savings in peak and average power, without requiring either a slower scan clock or blocking logic in the scan cells. We present a rigorous analysis to show that the proposed TRP technique reduces testing time compared to a conventional scan-based scheme. We also improve upon prior work on run-length coding by showing that test sets that minimize switching activity during scan shifting can be more efficiently compressed using alternating run-length codes. Experimental results for the larger ISCAS89 benchmarks and an IBM production circuit show that reduced test data volume, test application time, and low power-scan testing can indeed be achieved in all cases.